NRXN1 Deletion in Two Twins' Genotype and Phenotype: A Clinical Case and Literature Review - Monica Sciacca; Lidia Marino; Giovanna Vitaliti; Raffaele Falsaperla; Silvia Marino (MDPI AG, 2022)
In the literature, deletions in the 2p16.3 region of the neurexin gene (NRXN1) are associated with cognitive impairment, and other neuropsychiatric disorders, such as schizophrenia, autism, and Pitt-Hopkins-like syndrome 2. In this paper, we present twins with deletion 2p16.3 of the NRXN1 gene using a comparative genomic hybridization array. The two children had a dual diagnosis consisting of mild cognitive impairment and neurodevelopmental delay. Furthermore, they showed a dysmorphic phenotype characterized by facio-cranial disproportion, turricephalus, macrocrania, macrosomia, strabismus, and abnormal conformation of both auricles with low implantation. The genetic analysis of the family members showed the presence, in the father's genetic test, of a microdeletion of the short arm of chromosome 2, in the 2p16.3 region. Our case report can expand the knowledge on the genotype-phenotype association in carriers of 2p16.3 deletion and for genetic counseling that could help in the prevention and eventual treatment of this genetic condition. Newborn carriers should undergo neurobehavioral follow-ups for timely detection of warning signs.